Now, later, or not at all: personal and situational factors impacting burglars’ target choices - Roth, Jeffrey J. (Journal of crime and justice, 2017)
This study utilized hierarchical linear modeling to examine both situational factors and personal traits that influence burglars’ target selections. One unique aspect of this research was an assessment of the differences between immediate burglary (where a home is chosen and entered) and delayed burglary (where a home is chosen, but not entered until a later time). An additional distinctive feature was the modeling of the interactions between burglars’ personal traits and certain home features. To explore these issues, the researchers interviewed 52 male burglars in rural county jails in western Pennsylvania. Each participant answered questions about their personal traits and burglary experiences and viewed 50 pairs of home photographs. After viewing each pair of photographs, burglars were asked whether they would burglarize that home immediately, at a later time, or not at all. The researchers found several differences in the home features affecting immediate burglary target choices compared to delayed burglary ones. Additionally, burglars’ personal qualities interacted with some home features, indicating that burglars’ personal qualities can magnify or diminish the impact of home features on target selection.